Animal allergies - Tizard, Ian (Henry Stewart Talks, 2021)
The process of mast cell degranulation and IgE involvement, Allergic disease in animals, Type 1 hypersensitivity, Anaphylaxis, The pathogenesis of allergic dermatitis, Allergic dermatitis might not involve IgE, Diagnosis and treatment of allergic dermatitis, Allergy shots are the best long-term treatment